"Authentically Black, and Truly Catholic": A survey of the study on Black Catholics. Issue 10 (15th September 2017) - Winstead, Kevin
Abstract: Black Roman Catholics have been a contributing community to American culture as far back as the nation's founding. Despite nearly three million Black Catholics in the United States today, sociological research has given little consideration to this community. This review makes a case for more sociological focus on Black Catholicism. I review the available sociological research on Black Catholics and include a review of scholarship on Black Catholics from outside the discipline. I argue for the sociological importance of Black Catholicism to the examination of race, religion, and identity formation.